Pandangan Radikalisme dan Terorisme dalam Al-Qur’an - Alya Rohaly; Anisa Salsabila; Asya Noer Izzatin; Asep Abdul Muhyi (Gunung Djati Conference Series, 2023)
Radicalism and terrorism are still endless topics to be discussed and studied. As we already know, radicalism thrives in society, especially in an era of increasingly advanced technology. Various information is easy to access, ranging from good news to even bad news. The method used in this study is a qualitative research method which is a method by processing data into a descriptive form. Descriptive research itself is a research method that presents a complete picture of a phenomenon or situation. Meanwhile, in interpreting it, we use the maudu’i interpretation method for finding answer about a topic in the Qur’an. The method is to collect the verses of Qur’an related to topic or theme discussed, then arrange and explain the reasons for the revalation and the linkage of the verses to one another and then interpret them by taking the opinions of commentators.